Pensamiento escrito en escultura - Jiménez Deredia, Jorge (2004)
“Genesis Bridge of Light” is a sculpture located in the Garden of Sculptures of the Costa Rican Art Museum in San Jose. Its creation inspired Geppe Inserra to interview its author, Jorge Jimenez Deredia. Jimenez Deredia's answers help us perceive, at least partially, his philosophy and humanistic view of life, which is permeated by two main elements: the Boruca Culture and the European Renaissance. His work “A Christ for Limon”, located in the Atlantic province of Limon , Costa Rica , presents a hopeful vision of Christianity in the West. The current article is a passage from an unpublished book that is hereby presented for the benefit of Costa Rican education. This publication is possible through the authorization Jimenez Deredia has given to Licentiate Gina Marin-Rojas, National Arts Consultant for the Ministry of Public Education (MEP).